La participación en las comunidades rurales: abriendo espacios para la participación desde la escuela - Torres Victoria, Nancy (2008)
The article id based on the participation in the country school, It goes over the national and international legislation, is important to stand out the fact that this article establish questions that the personal teaching will affront if he wants to open a space to participate in country school. Besides it includes and develops the share capital concept and relate it whit the educational theme.